Gas diffusion on graphene surfaces. Issue 5 (20th January 2017) - Sun, Chengzhen; Bai, Bofeng
Abstract : Gas diffusion on graphene surfaces is a two-dimensional gas behavior, controlled not by the hopping mechanism but by molecular collisions. Abstract : Graphene provides a possibility where gas adsorption energy is comparable with molecular collision energy for physically adsorbed gases, resulting in the incompetence of the traditional hopping model to describe graphene-related surface diffusion phenomena. By calculating surface diffusion coefficients based on the Einstein equation, we exactly demonstrate that the gas diffusion on a graphene surface is a two-dimensional gas behavior mainly controlled by the collisions between adsorbed molecules. The surface diffusion on the graphene film just follows the bulk diffusion qualitatively, namely the diffusion coefficients decrease with increasing gas pressure. Quantitatively, the surface diffusion coefficients are lower than the bulk diffusion coefficients, predicted using the hard sphere model, owing to the restriction of graphene films. The reduction in diffusion coefficient is related to the simultaneously suppressed average frequency of molecular collisions and the average travelling distance between successive collisions. In addition, a lower diffusion coefficient on a hydrogen-functionalized graphene surface is identified, caused by the blocking effects of chemical functional groups.